Embedding additive particles in the sentence information structure: How L2 learners find their way through positional and prosodic patterns - Andorno, Cecilia Maria; Turco, Giuseppina (Linguistik Online, 2015)
Since 1986, Klein pinpointed the 'embedding problem' among the main tasks L2 learners have to cope with in L2 speaking, the term referring to the need of linking the semantic content of a sentence to the information already available in the ongoing discourse. Research in L2 acquisition has shown that, even when the lexical and morphosyntactic structures needed to express specific information configurations are in place, learners can still lack the ability to use them in the ongoing discourse according to target language preferences, thus sticking to their source language preferences (Carroll and Lambert 2003; Dimroth and Lambert 2008; Lambert, Carroll and von Stutterheim 2008).Use of additive particles can pose similar 'embedding' problems, as they typically occur in a peculiar, non-canonical information configuration, in which a given predicate – available in the ongoing discourse – is claimed to hold for a new referent, which is added to other – given, available – referents. Dimroth et al. (2010), comparing native speakers productions on the basis of the same narrative task (the Finite Story retelling), show that speakers of Germanic (Dutch, German) and Romance (French, Italian) languages differ in the way they embed additive particles in the sentence information structure. Our study focuses on the use of additive particles by intermediate learners of two language pairs (Italian L1 > German L2 and viceversa) in the Finite Story retelling. Results show that, in embedding additive particles (IT anche, GE auch) in the sentence structure, intermediate learners tend to adopt patterns that are compatible with the L1 both at positional and at prosodic level, thus partly discarding more target language-specific patterns.